2017
DOI: 10.4102/jsava.v88i0.1464
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cow-side diagnostic tests for subclinical mastitis of dairy cows in Musanze district, Rwanda

Abstract: Four subclinical mastitis diagnostic tests (the UdderCheck® test [a lactate dehydrogenase-based test], the California Mastitis Test [CMT], the Draminski® test [a conductivity-based test] and the PortaSCC® test [a portable somatic cell count-based test]) were compared in a study comprising crossbreed dairy cows (n = 30) during September and October 2015. Sensitivity and specificity of the CMT, Draminski® and UdderCheck® tests were compared with the PortaSCC® as reference. The CMT, Draminski® and UdderCheck® tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…Depending on the visibility of effects of inflammation of the mammary gland, which is attributable to the degree of inflammation, mastitis is classified as clinical or subclinical [22]. Clinical mastitis includes gross abnormality in milk, physical abnormalities of udder and abnormality of cow with systemic involvement while subclinical mastitis does not produce visible effects on udder or milk quality but has important effects on milk composition, mainly an increase in somatic cell counts [23,24]). While it is easy to detect clinical mastitis (seeing clotted milk), subclinical mastitis can only be demonstrated using various tests such as California Mastitis Test (CMT), Whiteside test (WST), Surf field mastitis test (SFMT), sodium lauryl sulphate test (SLST), Microscopic Somatic Cell Count (MSCC) and Electrical Conductivity (EC) [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the visibility of effects of inflammation of the mammary gland, which is attributable to the degree of inflammation, mastitis is classified as clinical or subclinical [22]. Clinical mastitis includes gross abnormality in milk, physical abnormalities of udder and abnormality of cow with systemic involvement while subclinical mastitis does not produce visible effects on udder or milk quality but has important effects on milk composition, mainly an increase in somatic cell counts [23,24]). While it is easy to detect clinical mastitis (seeing clotted milk), subclinical mastitis can only be demonstrated using various tests such as California Mastitis Test (CMT), Whiteside test (WST), Surf field mastitis test (SFMT), sodium lauryl sulphate test (SLST), Microscopic Somatic Cell Count (MSCC) and Electrical Conductivity (EC) [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…While it is easy to detect clinical mastitis (seeing clotted milk), subclinical mastitis can only be demonstrated using various tests such as California Mastitis Test (CMT), Whiteside test (WST), Surf field mastitis test (SFMT), sodium lauryl sulphate test (SLST), Microscopic Somatic Cell Count (MSCC) and Electrical Conductivity (EC) [25][26][27]. However, CMT has been recognized as a highly sensitive test to detect bovine subclinical mastitis [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…If that is not possible, the manufacturer recommends refrigerating the milk sample for up to 8 h and permitting the sample to warm to room temperature before testing. Peer-reviewed publications describing the performance of the PortaSCC test in bovine milk have recently become available (Balaji et al, 2016;Iraguha et al, 2017); however, neither study compared the test's performance with a suitable reference method. We hypothesized that the PortaSCC test would provide a more accurate method for diagnosing SCM and IMI in bovine milk than the CMT.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is very limited information on the antimicrobial susceptibility pattern of bacteria isolated from milk samples obtained from cases of bovine mastitis in Rwanda. Recently, two studies showed a high prevalence of mastitis in the Northern Province and the peri-urban areas of Kigali [12,13], but characterization of causative agents and antimicrobial susceptibility testing, both phenotypic and genotypic, have not been performed. Thus, the present study aims to fill these gaps by fully characterizing a collection of bovine staphylococci associated with clinical and subclinical mastitis from the Northern Province and Kigali the District of Rwanda.…”
Section: Introductionmentioning
confidence: 99%